'Going Live': An Exploration of Models of Peer, Supervisor Observation and Observation for Assessment. Issue 1 (1st January 2016) - Davys, Allyson Mary; Beddoe, Liz
Abstract : Over the past decade, live observation of practice has increasingly become a routine event for health and social service professions both nationally and internationally. For social work in particular, where a practice climate of risk mitigation and competence assurance prevails, the requirement for practice to be formally assessed to retain registration or licencing is becoming more common. Legislation in many countries mandates employers and professional bodies, to reassure the public about the qualifications and currency of practitioners' work. One way to achieve this is to require the demonstration of competence in 'real time' practice, with opportunities for professional development, formative and summative feedback and assessment. Such demonstrations may reawaken anxiety and doubt associated with earlier student assessment. The observers may also lack the knowledge, skills and confidence to perform them. We identify a range of observation opportunities, outlining the advantages of each and the differences between them. We describe a shift in the disposition in practice where the intent of observation moves from being primarily evaluative to become an active invitation for reflection, feedback and practice development. The article concludes with the outline of a model for observation which can fit each form of observation and which offers social workers purposeful engagement and ownership within the process.